An impact assessment tool to identify, quantify and select optimal social-economic, ecological and health outcomes of civic environmental management interventions, in Durban South Africa. (15th January 2022) - Davids, Rashieda; Rouget, Mathieu; Burger, Margaret; Mahood, Kirsten; Ditlhale, Ntswaki; Slotow, Rob
Abstract: Using an environmental impact assessment (EIA) methodology, we provide a novel approach to identify and assess social-ecological outcomes from civic ecology interventions. We quantified the impact significance of six civic (community led) interventions implemented by the Wise Wayz Water Care (WWWC) local community programme (solid waste management, water quality monitoring, invasive alien plant control, crop production, recycling and community engagement), in two communities, situated in urban to peri-urban/rural environments in Durban, South Africa. Interventions resulted in 37 outcomes, of which 36 were positive and one negative. The resulting significance scores from the impact assessment allowed for interventions and their outcomes to be compared. The socio-economic outcomes were the greatest (21), followed by ecological (11) and health outcomes (6). Outcomes included access to education and training; improved quality of life; improved terrestrial and aquatic ecosystems; increase in recreation and cultural uses of natural areas; reduced health risks and increased nutrition. The most significant ecological outcomes resulted from invasive alien plant control, followed by solid waste removal and water quality monitoring. The greatest health outcomes resulted from solid waste removal and vegetable gardens, whereas the greatest social-economic outcomes resulted from the general operation of WWWC, solid waste removal, and invasive alien plant control. We demonstrate that investments in natural areas can deliver not only on enhancements in ecosystems and their services, but also for local community socio-economic and health benefits. This study provides an intervention quantifying tool for practitioners to select optimal local management interventions, that can be aligned with desired outcomes related to specific community challenges and policy requirements. In so doing, this work shows the critical role that civic interventions play to ensure sustainability, and emphasises how social-ecological systems and ecosystem services perspectives can be used in practice towards achieving sustainable outcomes. Highlights: Environmental Impact Assessment of social-ecological outcomes from civic ecology. Novel approach to quantify sustainability outcomes of civic ecology interventions. A tool to select optimal management interventions for enhanced outcomes. By considering the 'whole system' civic ecology enhancements to well-being can be identified. Motivate for policy support of civic ecology to enhance outcomes and sustainability.